Interactive logic : selected papers from the 7th Augustus de Morgan Workshop, London - Benthem, Johan van, 1949-; Löwe, Benedikt; Gabbay, Dov M., 1945- (Texts in logic and games, 2007)
A collection of excellent research papers in logic, mathematics, computer science and game theory.